2015
DOI: 10.1088/0268-1242/31/1/014013
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and optical characterization of Bragg resonance luminescence porous silicon

Abstract: The synthesis and characterization of Bragg resonance luminescence porous silicon (BRL PS) exhibiting both optical reflectivity and strong narrow visible photoluminescence (PL) prepared from highly doped n-type silicon wafers through the electrochemical etching are reported. BRL PS showing the luminescence at 702 nm with an excitation wavelength of 400 nm was prepared by applying the current of 360 mA cm −2 for 1.6 s and 75 mA cm −2 for 3.6 s with 50 repeats in etching solution of 1:1 volume mixture of absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Here a shift to shorter wavelengths can be observed in all the experimental spectra which suggests that the SE refractive indices are not adequate. The calculations of the Q e -factor for these mirrors confirm the inadequacy of the SE measurements (see tables[1][2][3]. The difference between theory and experiment can be understood as a result of the complexity of modelling the PS nanostructure and the use of accurate SE data with complex models to estimate refractive indeces which afterwards are used in simple photonic structures.The blue-shift of the experimental reflectance spectra in figure4advises that the refractive index values must be smaller in order to displace the spectra to larger wavelengths to fit the theoretical spectra.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Here a shift to shorter wavelengths can be observed in all the experimental spectra which suggests that the SE refractive indices are not adequate. The calculations of the Q e -factor for these mirrors confirm the inadequacy of the SE measurements (see tables[1][2][3]. The difference between theory and experiment can be understood as a result of the complexity of modelling the PS nanostructure and the use of accurate SE data with complex models to estimate refractive indeces which afterwards are used in simple photonic structures.The blue-shift of the experimental reflectance spectra in figure4advises that the refractive index values must be smaller in order to displace the spectra to larger wavelengths to fit the theoretical spectra.…”
mentioning
confidence: 68%
“…For example, a Bragg-reflector is composed of a periodic stack of layers which alternate between high and low refractive indices with a high contrast between layers. If each layer satisfies the quarter wavelength condition, a selective mirror that reflects a central wavelength can be constructed [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in the literature that increasing radiative recombination via direct band-gap transitions and reducing the phonon-assisted indirect band-gap transitions can significantly enhance the photoluminescence [ 13 ]. Previous studies led by our group have demonstrated the successful fabrication of the DBR multilayer porous silicon devices exhibiting sharp PL peaks that arise from Bragg resonance in the visible range [ 14 ]. DBR devices are fabricated by alternating the square wave current between the high and low current values, leading to layers with low and high refractive indices, respectively.…”
Section: Introductionmentioning
confidence: 99%